Prevalence and correlates of tobacco and alcohol use among adolescents in Nawalpur district, Nepal - Sapkota, Narayan; Paneru, Damaru Prasad (Journal of Chitwan Medical College, 2021)
Background: Tobacco and alcohol use are major behavioral risk that contributes to the rapid increase in non communicable diseases in Nepal. This study aimed to assess prevalence and correlates of tobacco and alcohol use among adolescents. Methods: A cross-sectional study was conducted using the multi-stage probability sampling method. Self-administered questionnaire was used to collect the information among school going adolescent. Data was entered on Epi-data and analyzed using SPSS. Results: Prevalence of tobacco and alcohol consumption was 11.6% and 16.3% respectively. Male(AOR = 4.8, 95% CI: 2.0-11.5), older adolescents (AOR = 3.4, 95% CI: 1.6-7.2), pocket money of more than Rs. 350 (AOR 4.7, 95% CI 1.6-13.8) and living with other than family members (AOR 3.8, 95% CI 1.7-8.5) had higher odds of tobacco consumption whereas, male (AOR = 5.4, 95% CI: 2.5-11.5), late adolescents (AOR = 2.6, 95% CI: 1.3-5.0), pocket money of more than Rs. 350 (AOR = 5.4, 95% CI: 2.2-13.2) had higher odds of alcohol consumption. Conclusions: The study found that significant proportion of adolescents was involved in the consumption of tobacco and alcohol. Efforts are needed to find regulating and educational interventions to mitigate the risky behaviors and their health impacts on the adolescents.